Quantum Computing and Its Implications for Complex System Analysis - Kiran Iqbal; Omar Ahmad; Arnes Yuli Vandika (Research of Scientia Naturalis, 2024)
Quantum computing has emerged as a transformative technology capable of solving complex problems beyond the reach of classical computing. Its unique properties, such as superposition and entanglement, enable efficient processing of vast datasets, making it especially valuable for analyzing complex systems. This research aims to explore the implications of quantum computing for complex system analysis, particularly in fields such as physics, biology, and finance. The goal is to identify how quantum algorithms can enhance the understanding and modeling of intricate systems. A systematic literature review was conducted, examining recent advancements in quantum algorithms and their applications to complex system analysis. Comparative analyses were performed between classical and quantum computing approaches, focusing on specific case studies to illustrate the advantages of quantum solutions. The findings indicate that quantum computing significantly accelerates certain computations, leading to improved accuracy and efficiency in modeling complex systems. Case studies in quantum simulations of molecular interactions and financial modeling demonstrate substantial performance gains over classical methods. Quantum computing holds great promise for advancing the analysis of complex systems across various disciplines. Continued research and development in this area are essential to fully harness the capabilities of quantum technologies, ultimately leading to breakthroughs in understanding and solving complex problems.